Clinical outcomes and neurodevelopmental outcome of prenatally diagnosed agenesis of corpus callosum in single center of Korea - Kim, Sung Eun; Jang, Hye-In; Chang, Kylie Hae-jin; Sung, Ji-Hee; Lee, Jiwon; Lee, Jeehun; Choi, Suk-Joo; Oh, Soo-young; Roh, Cheong-Rae; Kim, Jong-Hwa (Obstetrics & gynecology science, 2017)
With recent advances and frequent use of prenatal ultrasound, the antenatal diagnosis of agenesis of the corpus callosum (ACC) is not rare in obstetrics practices. However, information regarding the long-term neurological outcome remains uncertain. The aim of this study was to investigate clinical outcomes of prenatally diagnosed ACC and to analyze postnatal neurodevelopmental outcomes of ACC neonates born in our single center. We retrospectively reviewed 56 cases of prenatally suspected ACC referred to our center. Fifty-six fetuses were diagnosed with ACC, and 12 of those were followed-up in our center until delivery. Of the remaining 44, 7 were delivered after being referred back to the original hospital, 23 were lost to follow-up, and 14 had unknown outcomes. Among all 56, 29 were considered to have isolated ACC and 27 were considered to have non-isolated ACC. Of the 10 live fetuses delivered in our center, four had isolated ACC, three had non-isolated ACC, and the rest had outcomes unrelated to ACC. Neurodevelopmental outcome was followed-up until approximately age 3 years. Of the four with isolated ACC, three (75%) had normal neurodevelopmental outcomes. Similar to other studies, the results of our single-center study included positive neurodevelopmental outcomes for those with isolated ACC. However, despite our endeavor to counsel patients with prenatally diagnosed ACC, the delivery rate in our center was quite low. Therefore, larger, multicenter, retrospective studies including long-term neurological development outcomes are crucial and urgently needed to provide better counseling.